2004
DOI: 10.1097/00002508-200409000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Personality Factors in the Explanation of Sex Differences in Pain Catastrophizing and Response to Experimental Pain

Abstract: The results suggest that sex differences in catastrophizing and pain responsivity are partially accounted for by the dispositional tendency to describe oneself as emotionally vulnerable. The findings also suggest that pain catastrophizing may be situational as well as dispositional.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
56
4
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(72 citation statements)
references
References 29 publications
9
56
4
3
Order By: Relevance
“…10,14,20,34,35,39,49 The current study found that personality and coping factors were significantly associated with the pain drawing area, supporting findings of prior studies. 5,18,24 Specifically, other studies have identified factors such as depression, 18 psychological health, 8 and nonorganic signs 5,24 as significantly associated with pain drawing area.…”
Section: Results Tsupporting
confidence: 88%
See 1 more Smart Citation
“…10,14,20,34,35,39,49 The current study found that personality and coping factors were significantly associated with the pain drawing area, supporting findings of prior studies. 5,18,24 Specifically, other studies have identified factors such as depression, 18 psychological health, 8 and nonorganic signs 5,24 as significantly associated with pain drawing area.…”
Section: Results Tsupporting
confidence: 88%
“…We hypothesized that no sex differences would exist for pain severity, as per previously published reports involving patients with chronic pain. 36 However, we believed there was the potential for females to report a larger area on the pain diagram based on literature that suggests that women have increased pain sensitivity to standard stimuli 10,14,15,20,35,49 and a study that suggests that women may be more willing to report pain. 36 3.…”
mentioning
confidence: 99%
“…Thus, patients' general pain attitudes could be crucial while giving scores. Thorn et al 19 stated that when participants are not in pain but are responding to such questionnaires, they make better judgements about what they think in a typical painful situation. For this reason, patients were asked to answer the questionnaires 1 week after debonding to avoid any connections with their ratings on PCS and their actual pain experience.…”
Section: Discussionmentioning
confidence: 99%
“…19 Brain MRI studies have shown that expectations of pain interact powerfully with brain mechanisms that alter the subjective pain experience, enabling positive expectations to reduce perceived pain by 28.4%. 25 Supporting this finding, Polat 22 mentioned that informing the patient and putting their trust in their doctors would help control the anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of self-perceived role identity on pain perception, here defined as the product of the brain's abstraction and elaboration of a nociceptive input (Basbaum and Jessell, 2000), has been investigated in gender role studies, including coping strategies (Keogh and Herdenfeldt, 2002), pain catastrophizing (Thorn et al, 2004), situational context (Kallai et al, 2004), gender role expectations (Robinson et al, 2001) and hyper-vigilance (Rollman et al, 2004) or anxiety (Edwards et al, 2000).…”
Section: Introductionmentioning
confidence: 99%